1999
DOI: 10.1080/00034989958366
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, placebo-controlled study of the efficacy of oral penicillin, diethylcarbamazine or local treatment of the affected limb in preventing acute adenolymphangitis in lymphoedema caused by brugian filariasis

Abstract: Acute attacks of adenolymphangitis (ADL) contribute significantly to the morbidity seen in cases of filarial lymphoedema. Such cases are now being treated with multiple courses of the antifilarial drug diethylcarbamazine (DEC), either alone or in combination with antibiotics or anti-inflammatory drugs, based on anecdotal experience. In this, the first double-blind, placebo-controlled study, 150 patients with lymphoedema caused by brugian filariasis, each of whom recalled two or more ADL attacks in the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 9 publications
4
20
0
Order By: Relevance
“…The rate of ADLA was lowest six months after enrollment, yet a decrease was sustained over the two year period of the study. These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rate of ADLA was lowest six months after enrollment, yet a decrease was sustained over the two year period of the study. These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14].…”
Section: Discussionsupporting
confidence: 91%
“…Persons with lymphatic dysfunction caused by LF may suffer from adenolymphangitis (ADLA) episodes characterized by swelling, inflammation of the limbs, fever, malaise and chills [1]. The frequency of ADLA episodes has been shown to increase with more advanced lymphedema and studies have concluded that ADLA episodes are a risk factor for lymphedema progression [2][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that, in addition to being a critical risk factor for progression of lymphedema [4][8], [13], [14], ADLA episodes are strongly associated with poor quality of life [10], [22][28]. Thus, reducing ADLA frequency is arguably the most important objective of lymphedema management in resource-poor countries.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were performed at 10 cm from the large toe and 12, 20, and 30 cm from the sole of the foot, as described elsewhere [10, 11]. Averages of the 4 measurements were determined before treatment and at follow-up.…”
Section: Methodsmentioning
confidence: 99%